Changes of lumbopelvic rythm during trunk extension in adolescent soccer players - Tojima, M.; Torii, S. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Hip-spine coordination (or lumbopelvic rhythm) can be used to assess the lower-limb and spine functions. We measured low-back pain (LBP) in adolescent soccer players before and after a 6-month period and divided them into four groups: no LBP both before and after the period, LBP before but not after 0,LB P after but not before (NP), and LBP both before and after. We used 3D motion analysis during trunk extension to measure the lumba spine and hip ranges of motion QOMs). During the 6-month follow-up, lumbar spine ROM decreased in the NP group. This group extended their lumbar spine excessively compared with the hip before the period, which could cause LBP, but decreased the extension after the period. Lumbar extension relative to hip extension decreased in the PN group, which could decrease the excessive load on the lumbar spine and eliminate LBP.